1997
DOI: 10.1016/s0886-3350(97)80241-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topical fluoroquinolones on corneal re-epithelialization after excimer laser keratectomy

Abstract: These data suggest that both ofloxacin and ciprofloxacin influence corneal wound healing in rabbits after laser keratectomy and that their healing rates did not differ. A white precipitate that appeared in the epithelial defect area in some rabbits treated with ciprofloxacin did not prevent closure of the defect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
3

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 15 publications
0
8
0
3
Order By: Relevance
“…Mallari et al (11) reported an increased incidence of corneal perforation after topical ofloxacin treatment for microbial keratitis, and that the perforations were not associated with any particular microbial isolate. Moreira et al (12) examined the effects of commercially prepared topical fluoroquinolones on the healing rate of epithelial defects in the rabbit cornea after excimer laser keratectomy. Their data suggested that both ofloxacin and ciprofloxacin significantly delayed corneal wound healing in rabbits after laser keratectomy and that their healing rates did not differ.…”
Section: Discussionmentioning
confidence: 99%
“…Mallari et al (11) reported an increased incidence of corneal perforation after topical ofloxacin treatment for microbial keratitis, and that the perforations were not associated with any particular microbial isolate. Moreira et al (12) examined the effects of commercially prepared topical fluoroquinolones on the healing rate of epithelial defects in the rabbit cornea after excimer laser keratectomy. Their data suggested that both ofloxacin and ciprofloxacin significantly delayed corneal wound healing in rabbits after laser keratectomy and that their healing rates did not differ.…”
Section: Discussionmentioning
confidence: 99%
“…[15] However, several in vitro and in vivo studies have demonstrated that both ciprofloxacin and ofloxacin eye drops significantly delay corneal wound healing. [7,8,16] In addition, ciprofloxacin hydrochloride 0.3% solution has demonstrated a tendency for precipitation with corneal crystal deposition, mainly in association with the pH dependent solubility of the eye drop formulation. [17,18] The above mentioned studies suggest that the current commercially available topical fluoroquinolone agents, and their accompanying preservatives, have cytotoxic effects on corneal cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that use of topical antibiotics is likely to interfere with wound healing in the immediate postoperative period [8][9][10]. However, it is equally understood that the use of antibiotic prophylaxis is needed for the prevention of potentially visually devastating infections.…”
Section: Discussionmentioning
confidence: 99%